(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the use of hyperbole in the works of Alisher Navoiy, an influential poet and writer of the 15th century in Central Asia. The study analyzes Navoiʼs poetic techniques and the role of hyperbole in his literary compositions. Through a comprehensive examination of selected poems and prose, this article aims to shed light on how Navoi employs hyperbolic language to enhance his artistic expression and convey profound emotions of his characters and his own. The findings contribute to a deeper understanding of Navoiʼs literary style and his impact on Central Asian literature.